De-terminants of entreprneurial career: Experience of polytechnic students - Awang, Amran; Ibrahim, Ima Ilyani; Ayub, Siti Azreena (Journal of Entrepreneurship, Business and Economics, 2014)
Purpose- This study focuses on the factors influencing students’ choice of selecting entrepreneurship as their career after graduation. The paper aims to gain more understanding of how personality traits, entrepreneurship knowledge-experience and current economic environment affect entrepre-neurial career among polytechnic students in Malaysia. Design/methodology/approach- A theoretical framework based on a literature review is developed. Empirical results were derived from a quantitative approach based on survey method and a cross sectional study. Hypothesis testing were executed where multiple regression analysis utilized to verify the direct relationship between independent variables and dependent variables. Findings- Personality traits and favorable economic environment were proven important in explain-ing students intention to choose entrepreneurial career as their career choice after they graduated from study. Research Implications- The results shall aid polytechnics management in formulating their curricu-lum and programs that fit students’ priorities that they shall choose their future undertaking as an entrepreneur. Malaysian public policy regarding higher education should consider some changes required in higher learning institutions in the country. Annual budget and higher learning institutions entrepreneurship programs shall be revised accordingly after considering the results of the study. Originality/value- Entrepreneurial intention inquiries in Malaysian institutions have been very limited and an established framework need more serious efforts. This study contributes to entrepreneu-rial intention body of knowledge. Research Paper Reference to this paper should be made as follows: Awang, A., Ibrahim, I. I., Ayub, S. A.(2014). ―De-terminants of entreprneurial career: Experience of polytechnic students‖, Journal of Entrepreneur-ship, Business and Economics, Vol. 2, No. 1, pp. 21–40.